Trends and impact of forest tenure reforms in Asia: cases from India, Indonesia, Lao PDR, Nepal and the Philippines - Dahal, G.R.; Adhikari, K.P. (2008)
For the last two decades, some countries in Asia have initiated progressive tenure reform in the forestry sector through transfer of management and use rights from the state to the local communities, indigenous groups, local government units, private sector and individual households. However, still around 92% of the forests in South and Southeast Asia are owned by the state, which manages it particularly for revenue generation and protection of environment (FAO 2006). Some of the devolved tenure models such as community forestry in Nepal and the Philippines and joint forest management in India are yielding promising results in terms of forest protection, but the livelihoods of the local communities are not fully recognized yet. Decentralization of forest management rights at household level such as in China, Vietnam and Cambodia is another encouraging model as it contributes to raising the incomes of poor households. However, the security of such rights in legal terms is questionable due to inconsistent policies and legal frameworks. Tenure reforms in Asia have had mixed results so far, but the reforms are heading towards addressing peoples’ livelihood needs on the one hand and protecting forest and environment on the other.